Analisis Dampak Lingkungan Proses Pengolahan Air Limbah Bandar Udara X Menggunakan Metode Life Cycle Assesment - Gita Gempita Nugroho; Restu Hikmah Ayu Murti (Fakultas Teknik Universitas Cenderawasih, 2024)
As a company engaged in transportation services, the airport located in East Java Province produces liquid waste with a quite large discharge in a day, which is 1120 m3. To treat the wastewater, the company has a Sewage Treatment Plant (STP) to adjust its quality standards before being discharged into the river. Every WWTP has the potential to cause environmental impact, both from the processing process and from the operation supporting tools. This study aims to analyze the three largest environmental impacts resulting from wastewater treatment activities at the airport in East Java, which are the impacts of Aquatic Ecotoxicity, Non-Renewable, and Ionizing Radiation. In addition, the author also provides recommendations for alternative STP operations that are more environmentally friendly. The approach used is the Life Cycle Assessment method using the OpenLCA application with the IMPACT 2002+ method.